MVP‐VSASL: measuring MicroVascular Pulsatility using velocity‐selective arterial spin labeling - Chen, Conan; Barnes, Ryan A.; Bangen, Katherine J.; Han, Fei; Pfeuffer, Josef; Wong, Eric C.; Liu, Thomas T.; Bolar, Divya S. (Magnetic resonance in medicine, 2025)
Purpose By leveraging the small‐vessel specificity of velocity‐selective arterial spin labeling (VSASL), we present a novel technique for measuring cerebral MicroVascular Pulsatility named MVP‐VSASL. Theory and Methods We present a theoretical model relating the pulsatile, cerebral blood flow‐driven VSASL signal to the microvascular pulsatility index (PI$$ PI $$), a widely used metric for quantifying cardiac‐dependent fluctuations. The model describes the dependence of the PI$$ PI $$ of VSASL signal (denoted PIVS$$ PI_{VS} $$) on bolus duration τ$$ τ $$ (an adjustable VSASL sequence parameter) and provides guidance for selecting a value of τ$$ τ $$ that maximizes the SNR of the PIVS$$ PI_{VS} $$ measurement. The model predictions were assessed in humans using data acquired with retrospectively cardiac‐gated VSASL sequences over a broad range of τ$$ τ $$ values. In vivo measurements were also used to demonstrate the feasibility of whole‐brain voxel‐wise pulsatility mapping, assess intrasession repeatability of PIVS$$ PI_{VS} $$, and illustrate the potential of this method to explore an association with age. Results The theoretical model showed excellent agreement to the empirical data in a gray matter region of interest (average R2$$ R^2 $$ value of 0.898 ±$$ ± $$ 0.107 across six subjects). We further showed excellent intrasession repeatability of the pulsatility measurement (ICC=0.960$$ ICC=0.960 $$, p<0.001$$ p<0.001 $$) and the potential to characterize associations with age (r=0.554$$ r=0.554 $$, p=0.021$$ p=0.021 $$). Conclusion We have introduced a novel, VSASL‐based cerebral microvascular pulsatility technique, which may facilitate investigation of cognitive disorders where damage to the microvasculature has been implicated.